Efficiency of Courts in China – Does Location Matter? - Xiaoge Dong (University of Hamburg, Institute of Law and Economics (ILE), 2021)
In this paper, we focus on determinants of judicial efficiency in China, with efficiency estimates of district courts obtained from data envelopment analysis (DEA). Our dataset comprises 1584 local courts pooled from the year 2014 - 2017. Controlling for local economic development level as well as the financial status and staff quality of local courts, we find a significant and robust impact of the location of local courts. More specifically, the performance of a court will be better when it is located in/closer to a higher city tier, the city center, the city government, or the provincial government even if the economic development of such areas is no better than others. Such courts probably receive (in)-direct political support and favorable local policy. Our result thus also has implications for judicial independence in China. Although the Chinese Central Government has been trying to separate the local legal system from local politics, local courts are still being affected by geopolitical factors in reality.
Keywords: K1; K40; K30; N45; P21; P37; 330; Chinese Court system; Court efficiency; data envelopment analysis; geopolitics